Rising obesity and expanding waistlines in schoolchildren: a cohort study. Issue 3 (20th February 2004) - Rudolf, M C J; Greenwood, D C; Cole, T J; Levine, R; Sahota, P; Walker, J; Holland, P; Cade, J; Truscott, J
Abstract : A cohort of schoolchildren was followed up over 6 years from 1996 to 2001. In the final year, 315 of 500 targeted children were measured. Body mass index (BMI) increased substantially over time (p<0.001), indicating a further rise in obesity into the secondary school years. Two new indicators of obesity were also measured. Waist circumference scores rose as substantially as BMI (p<0.001), and may be of particular significance given the association between abdominal girth in adults and cardiovascular morbidity. International Obesity Task Force measures were found to be more stringent than previous criteria, with no significant change noted over the time period.